1997
DOI: 10.4315/0362-028x-60.7.746
|View full text |Cite
|
Sign up to set email alerts
|

Population Changes and Verotoxin Production of Enterohemorrhagic Escherichia coli Strains Inoculated in Milk and Ground Beef Held at Low Temperatures

Abstract: This study investigated the influence of low temperature and background flora on growth and verotoxin production by strains of enterohemorrhagic Escherichia coli in milk and ground beef. In the presence of no or low background flora, there was growth of the strains at 8°C. High background flora in ground beef inhibited growth at this temperature. In the foods held at low temperatures, only small amounts of verotoxin were detected; however, even at the optimum 37°C, there was still relatively little verotoxin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 0 publications
2
15
0
1
Order By: Relevance
“…E. coli O157:H7 in ground beef has been demonstrated to survive for 9 months at À20 C with little change in population (Doyle and Schoeni, 1984). Although growth in ground beef was suppressed, EHEC cells retained their viability, even when stored at low temperature (5 C) (Palumbo et al, 1997). These findings are in accordance with several studies on fresh produce (Yamamoto and Harris, 2001;Strawn and Danyluk, 2010;Huang et al, 2013), and suggests that the ability of pathogens to survive under freezing conditions for a long period of time cannot be underestimated, making proper processing vital.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…E. coli O157:H7 in ground beef has been demonstrated to survive for 9 months at À20 C with little change in population (Doyle and Schoeni, 1984). Although growth in ground beef was suppressed, EHEC cells retained their viability, even when stored at low temperature (5 C) (Palumbo et al, 1997). These findings are in accordance with several studies on fresh produce (Yamamoto and Harris, 2001;Strawn and Danyluk, 2010;Huang et al, 2013), and suggests that the ability of pathogens to survive under freezing conditions for a long period of time cannot be underestimated, making proper processing vital.…”
Section: Introductionsupporting
confidence: 71%
“…These findings are in accordance with several studies on fresh produce (Yamamoto and Harris, 2001;Strawn and Danyluk, 2010;Huang et al, 2013), and suggests that the ability of pathogens to survive under freezing conditions for a long period of time cannot be underestimated, making proper processing vital. With some exceptions of the survival of E. coli in ground beef during frozen or refrigerated storage (Doyle and Schoeni, 1984;Palumbo et al, 1997;Ansay et al, 1999), there are few studies on the effects of frozen storage on the behavior of EHEC in frozen meat products.…”
Section: Introductionmentioning
confidence: 97%
“…McIngvale et al. (2002) and Palumbo et al. (1997) showed that high levels of iron and reduced temperature reduced Stx1 production; however, studies by Wagner et al.…”
Section: Discussionmentioning
confidence: 99%
“…This trend was not seen when we compared the predicted ⌬ log CFU values (from ground turkey) with the observed ⌬ log CFU values from unground poultry products. Fourth, some pathogen strains may be capable of growth at temperatures slightly above or below the limits of THERM (11), although the ability of hemorrhagic E. coli to grow at 8ЊC in ground beef has been reported to decrease when high levels of background organisms are present (12).…”
Section: Table 7 Observed and Predicted (Therm) Growth Of Escherichimentioning
confidence: 99%